Support group for families with children in a pediatric intensive care unit - Moraes,Erika Sana (2022)
ABSTRACT Objective: To describe the process of creating and implementing a support group for families with children in a pediatric intensive care unit. Methods: A professional experience report described using a management and planning tool. Results: This is a pioneering initiative in the hospital. The application of the tool enabled the delineation of the scope, justification, location, frequency, responsible persons, approach, and budget. After its implementation, the group enables significant interaction between health professionals-families and families-families, favoring the formation of therapeutic bonds and stimulating social and emotional support networks. Conclusion: The tool effectively planned the group and highlighted its effects on family coping and the relationships between professionals and families.